Focal species of birds in European crops for higher tier pesticide risk assessment. (27th January 2014) - Dietzen, Christian; Edwards, Peter J; Wolf, Christian; Ludwigs, Jan‐Dieter; Luttik, Robert
ABSTRACT Focal species have been defined by the European Food Safety Authority (EFSA) as real species that represent others in a crop resulting from their potential higher level of exposure to pesticides. As such they are the most appropriate species for refining estimates of exposure further, through, for example, radio tracking and dietary studies. Plant protection product manufacturers collectively commissioned many studies in Europe, according to the EFSA guidelines, to identify focal species in different crops that may be used in risk assessments for spray applications of pesticides. Using frequency of occurrence in crops and risk‐based criteria for exposure, all studies have been reviewed to identify if possible at least 1 focal species per feeding guild, per crop in the new registration zones for southern and central Europe. Some focal species repeatedly appeared across a wide range of arable or tree crops but not both, demonstrating broad adaptation to these 2 different crop structures. Many have widespread distributions, for example, 15 of the focal species have a distribution covering all agricultural regions of Europe (northern, central, and southern zones). Three species, corn bunting, serin, and tree sparrow, are restricted to the central and southern zones, whereas another 4 species, Sardinian and fan‐tailed warbler, and crested and short‐toed lark, are essentially restricted to the southern zone. The authors consider the focal species identified as suitable for risk assessment in Europe at the zonal level and for further refinement of exposure through studies, such as radio tracking or diet analysis, if necessary. Integr Environ Assess Manag 2014;10:247–259. © 2013 SETAC